Torsional interaction analysis of a turbine generator in a series capacitor compensated power system undergoing subsynchronous resonance - Viray, Zigfred Nino C. (2004)
Improved power transfer capability, increase in steady state stability limits and decrease in installation of new and costly transmission lines are few of the benefits of a series capacitor compensated power system. However, series capacitor may lead to the introduction or excitation of undesirable oscillations that may result to decrease of the usable life, loss of synchronization or worst shaft destruction of a turbine generator. This unwanted phenomenon is termed as Subsynchronous Resonance (SSR). This paper will focus on the more important and complex aspect of the SSR phenomenon, which is Torsional Interaction (TI). It involves the oscillation of the generator rotor at a natural mechanical frequency that results in the modulation of the generator voltage. If this frequency is near the network's natural frequency, significant energy exchange between the electric system and turbine-generator below the synchronous frequency occurs that may lead to shaft damage. The machine's mechanical system will be modeled as a series of shaft sections by a mass-spring-damper system. Eigenvalue Analysis will be used to analyze the phenomenon and will be verified by an Electromagnetic Transient Program (EMTP).